A group‐choose algorithm supporting virtual organization creation for workflow deployment in cloud environment. (25th January 2013) - Pan, Maolin; Li, MiaoMiao; Yu, Yang; Chen, Jinjun; Ranjan, Rajiv
ABSTRACT Virtual organization (VO) is a main organizational paradigm for enterprises to collaborate in the rapidly changing environment. However, finding partners for VO creation has great challenges on Internet, because a VO initiator is blinded without enough partners' information. The problem of VO creation in cloud environment is discussed. A VO creating algorithm (called Group‐Choose) based on reputation system is presented to help initiator minimize the operating risk on Internet. In the algorithm, a VO initiator aggregates partners' trust evaluations of candidates to select new partners for VO, instead of evaluating candidate's trust only by itself. The third‐party assessment and Time Slide Window are used in peer‐to‐peer trust evaluation to make the model more adaptive in the dynamic environment. The proposed method focuses on the reputation data, without taking other factors into consideration. Compared with PathTrust and PeerTrust, the Group‐Choose algorithm for VO creation has better performance in resisting conspiracy attack and periodic attack. Copyright © 2013 John Wiley & Sons, Ltd.